Correlation of RELL1 Expression with Clinical Pathological Characteristics and Prognosis of Patients with Colon Cancer - Jie FENG; Ya′nan ZHANG; Nuo CHENG; Yan CHU; Yunhai SHEN; Qincong PAN (Zhongliu Fangzhi Yanjiu, 2024)
ObjectiveTo explore the correlation of RELL1 expression with clinical pathological features and prognosis of patients with colon cancer. MethodsImmunohistochemical experiments of the RELL1 protein were performed on tissue chips from 80 colon cancer tissues and 80 adjacent tissues. The relationship between different expression levels of RELL1 protein and clinical pathological parameters was compared. Univariate and multivariate Cox risk proportional regression analyses were conducted on factors affecting the survival of patients with colon cancer. Kaplan-Meier survival curve analysis was conducted on the survival rates of patients with colon cancer and different levels of RELL1 expression. Log rank test was performed to evaluate differences in survival rates. ResultsThe expression of RELL1 in colon cancer tissues was lower than that in adjacent tissues (P<0.05). The expression of RELL1 in cancer tissues is correlated with TNM stage and N stage (P<0.05). The 3-year overall survival (OS) rate of colon cancer patients with high RELL1 expression was higher than that of patients with low RELL1 expression (P<0.05). Multivariate Cox regression analysis showed that low RELL1 expression, advanced age, and high TNM stage were risk factors for poor prognosis in patients with colon cancer (P<0.05). ConclusionThe expression of RELL1 is downregulated in colon cancer tissue, and the low RELL1 expression, advanced age, and high TNM stage can lead to adverse outcomes in patients.